MONITORING SUHU RUANGAN SERVER DENGAN FUZZY LOGIC METODE SUGENO MENGGUNAKAN ARDUINO DAN SMS - Rossy Rosdian Abdullah; Agung Wibowo (Universitas Bina Sarana Informatika Kota Sukabumi, 2014)
Apart from being a Server Control Center is also the access gateway to the outside world, to maintain good communication access necessary servermaintenance of adequate physical security monitoring, such as server space and server room temperature. When the room temperature is too hot it will affect server performance and server equipment will be easily damaged, use of temperature sensors as the sensor becomes one of the solutions used. Temperature readings using the arduino, arduino is able to read 10bit analog signal , arduino using the ATMega328p in use to display temperature in the LCD PCD8544. Through fuzzy logic that his Input in the form of Crips Error and different Error, the system will control the fan according to the temperature of the sugeno method FIS server space in accordance with imposed according to company policies, if room temperature exceeds the specified threshold control method and system by itself is not successful, the arduino will give orders (AT Command) on the GSM Modem, to give a warning in the form of SMS to the clerk and overheating when the LCD will Flash with the words